Telling tails: Selective pressures acting on investment in lizard tails - Fleming, P.; Valentine, L.; Bateman, Bill (The University of Chicago Press, 2013)
Caudal autotomy is a common defense mechanism in lizards, where the animal may lose part or all of its tail to escape entrapment. Lizards show an immense variety in the degree of investment in a tail (i.e., length) across species, with tails of some species up to three or four times body length (snout-vent length [SVL]). Additionally, body size and form also vary dramatically, including variation in leg development and robustness and length of the body and tail. Autotomy is therefore likely to have fundamentally different effects on the overall body form and function in different species, which may be reflected directly in the incidence of lost/regenerating tails within populations or, over a longer period, in terms of relative tail length for different species. We recorded data (literature, museum specimens, field data) for relative tail length (n = 350 species) and the incidence of lost/regenerating tails (n = 246 species). We compared these (taking phylogeny into account) with intrinsic factors that have been proposed to influence selective pressures acting on caudal autotomy, including body form (robustness, body length, leg development, and tail specialization) and ecology (foraging behavior, physical and temporal niches), in an attempt to identify patterns that might reflect adaptive responses to these different factors. More gracile species have relatively longer tails (all 350 spp., P < 0.001; also significant for five of the six families tested separately), as do longer (all species, P < 0.001; Iguanidae, P < 0.05; Lacertidae, P < 0.001; Scindidae, P < 0.001), climbing (all species, P < 0.05), and diurnal (all species P < 0.01; Pygopodidae, P< 0.01) species; geckos without specialized tails (P < 0.05); or active-foraging skinks (P < 0.05). We also found some relationships with the data for caudal autotomy, with more lost/regenerating tails for nocturnal lizards (all 246 spp., P < 0.01; Scindidae, P < 0.05), larger skinks (P < 0.05), climbing geckos (P < 0.05), or active foraging iguanids (P < 0.05). The selective advantage of investing in a relatively longer tail may be due to locomotor mechanics, although the patterns observed are also largely consistent with predictions based on predation pressure.